Evaluation and Management of Adolescents With a Stiff Flatfoot. Issue 16 (15th August 2022) - Ford, Samuel E.; Zide, Jacob R.; Riccio, Anthony I.
Abstract : While flatfeet are normal in children, persistence into adolescence with associated pain or asymmetry warrants additional evaluation. Rigidity of a flatfoot deformity, whether a clinical report or evident on examination, should raise suspicion for pathology. The differential diagnosis includes tarsal coalition, neurogenic planovalgus, and peroneal spasticity. History must include pointed inquiry into birth and neurologic histories to probe for a source of central spasticity. Examination must include standing assessment of hindfoot and midfoot alignment. Hindfoot rigidity may be assessed by the double limb heel rise test and manual examination. Radiographs should include standing ankle (anterior-posterior and mortise) and whole foot (anterior-posterior, external rotation oblique, and lateral) images. Magnetic resonance imaging is more sensitive for identifying coalitions and better characterizes adjacent cartilage, subchondral edema, and tendon pathology, yet CT better characterizes the anatomy of a bony coalition. Conservative treatments are pathology-dependent and play a more prominent role in neurogenic or peroneal spastic flatfoot. Surgical management of coalitions is centered on coalition resection coupled with arthrodesis in the case of a talocalcaneal coalition with a dysplastic subtalar joint; concomitant planovalgus reconstruction is considered on a case-by-case basis.